2013
DOI: 10.1007/s00726-013-1574-1
|View full text |Cite
|
Sign up to set email alerts
|

Activation of polyamine catabolic enzymes involved in diverse responses against epibrassinolide-induced apoptosis in LNCaP and DU145 prostate cancer cell lines

Abstract: Epibrassinolide (EBR) is a biologically active compound of the brassinosteroids, steroid-derived plant growth regulator family. Generally, brassinosteroids are known for their cell expansion and cell division-promoting roles. Recently, EBR was shown as a potential apoptotic inducer in various cancer cells without affecting the non-tumor cell growth. Androgen signaling controls cell proliferation through the interaction with the androgen receptor (AR) in the prostate gland. Initially, the development of prostat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
21
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 30 publications
(27 citation statements)
references
References 30 publications
6
21
0
Order By: Relevance
“…Surprisingly, FHC and MEF cells continued to live in media with the same EBR concentration during the exact time points as cancer cells. These data, suggesting that normal cells were poorly affected by EBR treatment, were correlating with our previous findings on EBR not cytotoxic to PNT1a normal prostate epithelial cells …”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Surprisingly, FHC and MEF cells continued to live in media with the same EBR concentration during the exact time points as cancer cells. These data, suggesting that normal cells were poorly affected by EBR treatment, were correlating with our previous findings on EBR not cytotoxic to PNT1a normal prostate epithelial cells …”
Section: Discussionsupporting
confidence: 92%
“…Although EBR, one of the brassinosteroid family members, has been shown to strongly promote cell expansion and proliferation in plant cells, its apoptotic function by affecting many important cellular mechanisms, such as Bcl‐2 family members, cell survival kinases, polyamine metabolic enzymes, and cell cycle regulatory proteins, was demonstrated . Our latest findings also indicated that CALR, a key chaperone protein playing role in protein folding in the ER lumen, was drastically affected by EBR treatment in prostate cancer cells .…”
Section: Discussionmentioning
confidence: 73%
See 1 more Smart Citation
“…Apoptotic effects of brassinolide on human prostate cancer PC-3 cells was shown to be associated with caspases-3 activation [112]. EBl-induced apoptosis of LNCaP and DU-145 cancer cells was accompanied by a decrease of intracellular polyamine levels and a significant down-regulation of ornithine decarboxylase [113].…”
Section: Anticancer Effectsmentioning
confidence: 98%
“…Apoptotic cell death induced by epibrassinolide (EBR), a biologically active compound of the brassinosteroids, related to polyamine biosynthetic and catabolic pathways in LNCaP (AR? ), DU145 (AR-) prostate cancer cell lines and PNT1,a normal prostate epithelial cell line, has been investigated (Obakan et al (2013). Induction of apoptotic cell death was observed in prostate cancer cell lines after EBR treatment.…”
Section: Editorialmentioning
confidence: 99%